PENGARUH PEMBELAJARAN VIRTUAL AL-QUR'AN HADITS TERHADAP REVOLUSI MENTAL RELIGIUS PESERTA DIDIK (STUDI KASUS MAN 01 PATI) - Laila Nurul Hidayah; Ashif Az Zafi (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2021)
This research aims to identify and produce valid information about the religious mental of students in the online learning process from home due to the COVID19 pandemic. The research method used are quantitative research method and case study approach to the activities of the teaching and learning process and its influence on the religious character of students in MA Negeri 01 Pati. The research results obtained some problems faced by students, teachers and guardians in online learning activities from home, including the lack of mastery of modern technology, additional expenses for buying internet quotas,Â  reduced interaction, communication and socialization between teachers, students, and studentsâ€™ guardians. So it is very influential on the religious mental of students, among others, the prayers are not on time, the prayers are not complete for 5 times, the sunnah prayers, reading the Al-Quran is reduced, as well as their social attitudes. Because usually there are teachers who directly provide examples, guide and remind them, now the parents must replace them, teachers only remind and control through communication tools.Keywords: Mental Character, Learning From Home, Covid-19 Pandemic